Effects of Chlorides on Corrosion of Simulated Reinforced Blended Cement Mortars - Wachira, Jackson M. (Hindawi, 2019)
Cementitious materials are subject to degradation when subjected to corrosive chloride media. This paper reports the experimental results on corrosion studies conducted on a potential cementitious material, PCDC, made from a blend of 55 % Ordinary Portland Cement (OPC), Dried Calcium Carbide Residue (DCCR), and an incineration mix of Rice Husks (RH), Spent Beaching Earth (SBE), and Ground Reject Bricks (BB). The experiments were run along 100 % OPC. Different w/c were used. Corrosion current densities using linear polarisation resistance (LPR) and corrosion potentialsmeasurements versus saturated calomel electrode were used for the determination of corrosion rates and potentials, respectively, for simulated reinforcement at different depths of cover in the cement mortars.The results showed that PCDC exhibited higher corrosion current densities over all depths of covers and early attainment of active corrosion than the control cements. In conclusion, PCDC and OPC can be used in a similar corrosive media during construction.